Using affinity set on mining the necessity of computed tomography scanning - Chen , Yuh Wen; Larbani, Moussa; Li, Tzung Hung; Chen, Chao-Wen (IEEE, 2009)
Computed tomography (CT) is a medical imaging method of tomography. Digital geometry processing is used to generate a three-dimensional image of the inside of a patient from a large series of two-dimensional X-ray images taken around a single axis of rotation. The scanning ofCT has become an important tool in medical imaging to supplement X-rays and medical ultrasonography. Although it is expensive, it is the best tool to diagnose a large number of different disease entities; especially, for the trauma patients in emergency room. In this study, the trauma patients, who were treated by the CT scanning are collected in order to discover the critical knowledge; that is, what characteristics of trauma patients would lead to the necessity of CT scanning? The data mining model of affinity set and neural network (NN) are both used for resolution and comparison. Finally, studying results show that he affinity model performs better than the NN model, but the collected data lacks the explanatory power in practices. Thus, a further research is necessary.